Freeze-thaw cycles induce content exchange between cell-sized lipid vesicles. (18th May 2018) - Litschel, Thomas; Ganzinger, Kristina A; Movinkel, Torgeir; Heymann, Michael; Robinson, Tom; Mutschler, Hannes; Schwille, Petra
Abstract: Early protocells are commonly assumed to consist of an amphiphilic membrane enclosing an RNA-based self-replicating genetic system and a primitive metabolism without protein enzymes. Thus, protocell evolution must have relied on simple physicochemical self-organization processes within and across such vesicular structures. We investigate freeze-thaw (FT) cycling as a potential environmental driver for the necessary content exchange between vesicles. To this end, we developed a conceptually simple yet statistically powerful high-throughput procedure based on nucleic acid-containing giant unilamellar vesicles (GUVs) as model protocells. GUVs are formed by emulsion transfer in glass bottom microtiter plates and hence can be manipulated and monitored by fluorescence microscopy without additional pipetting and sample handling steps. This new protocol greatly minimizes artefacts, such as unintended GUV rupture or fusion by shear forces. Using DNA-encapsulating phospholipid GUVs fabricated by this method, we quantified the extent of content mixing between GUVs under different FT conditions. We found evidence of nucleic acid exchange in all detected vesicles if fast freezing of GUVs at −80 °C is followed by slow thawing at room temperature. In contrast, slow freezing and fast thawing both adversely affected content mixing. Surprisingly, and in contrast to previous reports for FT-induced content mixing, we found that the content is not exchanged through vesicle fusion and fission, but that vesicles largely maintain their membrane identity and even large molecules are exchanged via diffusion across the membranes. Our approach supports efficient screening of prebiotically plausible molecules and environmental conditions, to yield universal mechanistic insights into how cellular life may have emerged.